2018
DOI: 10.3390/molecules23030657
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Macromolecules: From Synthesis to Applications

Abstract: Hyperbranched macromolecules (HMs, also called hyperbranched polymers) are highly branched three-dimensional (3D) structures in which all bonds converge to a focal point or core, and which have a multiplicity of reactive chain-ends. This review summarizes major types of synthetic strategies exploited to produce HMs, including the step-growth polycondensation, the self-condensing vinyl polymerization and ring opening polymerization. Compared to linear analogues, the globular and dendritic architectures of HMs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 141 publications
(167 reference statements)
0
49
0
Order By: Relevance
“…HB polymers have been used in various fields of technologies such as biological applications (therapeutic, protein delivery, antimicrobial, etc. ), coatings, catalysis, nanotechnology, additives, sensors (chemical and bio), energy storage applications (thermal energy storage, rechargeable batteries, and solar cells) and electroluminescence applications …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…HB polymers have been used in various fields of technologies such as biological applications (therapeutic, protein delivery, antimicrobial, etc. ), coatings, catalysis, nanotechnology, additives, sensors (chemical and bio), energy storage applications (thermal energy storage, rechargeable batteries, and solar cells) and electroluminescence applications …”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION A branched polymer structure was defined as a nonlinear polymer consisted of atoms taking place more than one backbone chain spreading from branch points. [1][2][3][4][5][6][7][8][9] The branching in the polymer backbone is a useful structural variable that can be used advantageously to modify the polymer physical properties and processing characteristics because of changing the melt, solution, and solid-state properties of the polymer. It has been shown that branching results in a more compact structure in comparison to the linear counterpart with similar molecular weight, due to its high segment density, which affects the crystalline, mechanical, and viscoelastic properties of the polymer.…”
mentioning
confidence: 99%
See 3 more Smart Citations